Christian Discourse in the Tragedy Comedy by Feofan Prokopovich “Vladimir” - N. P. Zhilina (Научный диалог, 2021)
The central work of art by the outstanding Russian thinker of the early 18th century, philosopher, theologian and writer, associate of Peter I is examined in the article. The novelty of the study is that until now, religious discourse has not been subjected to systemic analysis. The relevance of the study is determined by the need to comprehend Christian motives and reminiscences, as well as the Gospel text as part of the play. Various plot situations are brought into consideration, giving the author the opportunity to show that in the comparison of two worldviews the opposite of their axiological systems is revealed. It is established that the opposition “Christianity / paganism”, which forms the basis of the artistic conflict, correlates in the play with the oppositions “life / death”, “truth / falsehood”, “spiritual / material”, “heavenly / earthly”, “salvation / death”. It has been proven that an important place is given to the play of Christian anthropology, as evidenced by the presentation of the biblical story of the expulsion of the first people from paradise, as well as the depiction of a difficult spiritual struggle that the protagonist experiences when deciding on a change of faith. A systematic analysis leads the author to the conclusion that the play uses the compositional principle that was used in the ancient fine arts and received in the works of Fr. Pavel Florensky called “reverse perspective”.